PWE-435 Abdominal tuberculosis – 10 year experience from a uk district general hospital. (22nd June 2015) - Ford, M; Boyd-Carson, H; Disney, BR; Doherty, M; Ishaq, S
Abstract : Introduction: The rate of tuberculosis has remained relatively stable over the past decade. However, the proportion of cases with extra-pulmonary disease has increased from 40.9% to 47.9%. Multiple studies have shown that diagnosis of abdominal tuberculosis (ATB) is often delayed due to non-specific symptoms in patients. The aim of this study was to examine a selection of patients from a UK district general hospital with a diagnosis of ATB and the process in which that diagnosis was reached. Method: We performed a retrospective review of all patients at Russells Hall Hospital, Dudley, who had a diagnosis of ATB between 2004 and 2014. Demographic, clinical, laboratory and radiographical findings were collated including the time delay between hospital presentation and diagnosis. Results: Sixteen cases of ATB were identified with a median age of 38.5 years at time of diagnosis (range 22–73 years) with a male gender of 56%. The majority (87.5%) were of non-white background; South Asian (69%), Afrocaribbean (19%) and White British (12%). The commonest features were abdominal pain (62.5%), weight loss (50%) and fevers (50%). The time between first presentation to hospital and diagnosis ranged from 2 days to 3 years. Basic investigations revealed mean haemoglobin of 11.9 ± 1.7 g/dL, CRP of 109 ± 92 mg/L, alkaline phosphatase of 200 ± 160 IU/L, and albumin of 37.1 ± 6.5 g/L. The chest x-ray was normal in 11 patients; abnormalities seen were consolidation in 3 patients and a cavitating lesion in 1 patient. One patient did not have an x-ray. There was a wide range of sites of disease including small bowel (25%), peritoneum (25%), lymph nodes (18.75%), appendix (12.5%), liver (12.5%) and omentum (6.25%). Tuberculin test was only performed in three patients and all of which were positive. Diagnosis was based on histology (43.75%), imaging (31.25%), microbiology (6.25%), or a combination of clinical suspicion and imaging or appearances at surgery (18.75%). The majority who received treatment (9/14) were given Rifater plus ethambutol. The remaining five patients all received a different combination of antituberculous treatment (Rifater alone, Rifinah ± Pyrazinamide and Ethambutol, Rifampicin/Isoniazid/Pyrazinamide ± Ethambutol). Two patients did not receive treatment as their diagnosis was made post-mortem. Of the sixteen patients, ten were treated and discharged, three died, two have on-going review and one was lost to follow up. Conclusion: ATB is a difficult diagnosis to make and there can be a significant time delay between symptom onset and diagnosis as the symptoms can be varied and insidious in nature. It is an easily treatable condition and a combination of abdominal pain, fevers and weight loss in a non-Caucasian patient should raise suspicion and warrants further investigation. Disclosure of interest: None Declared.